Ω3-Polyunsaturated fatty acids for heart failure: Effects of dose on efficacy and novel signaling through free fatty acid receptor 4. (February 2017) - O'Connell, Timothy D.; Block, Robert C.; Huang, Shue P.; Shearer, Gregory C.
Abstract: Heart failure (HF) affects 5.7 million in the U.S., and despite well-established pharmacologic therapy, the 5-year mortality rate remains near 50%. Furthermore, the mortality rate for HF has not declined in years, highlighting the need for new therapeutic options. Omega-3 polyunsaturated fatty acids (ω3-PUFAs), eicosapentaenoic acid (EPA) and docosahexaenoic acid (DHA), are important regulators of cardiovascular health. However, questions of efficacy and mechanism of action have made the use of ω3-PUFAs in all cardiovascular disease (CVD) controversial. Here, we review recent studies in animal models of HF indicating that ω3-PUFAs, particularly EPA, are cardioprotective, with the results indicating a threshold for efficacy. We also examine clinical studies suggesting that ω3-PUFAs improve outcomes in patients with HF. Due to the relatively small number of clinical studies of ω3-PUFAs in HF, we discuss EPA concentration-dependency on outcomes in clinical trials of CVD to gain insight into the perceived questionable efficacy of ω3-PUFAs clinically, with the results again indicating a threshold for efficacy. Ultimately, we suggest that the main failing of ω3-PUFAs in clinical trials might be a failure to reach a therapeutically effective concentration. We also examine mechanistic studies suggesting that ω3-PUFAs signal through free fatty acid receptor 4 (Ffar4), a G-protein coupled receptor (GPR) for long-chain fatty acids (FA), thereby identifying an entirely novel mechanism of action for ω3-PUFA mediated cardioprotection. Finally, based on mechanistic animal studies suggesting that EPA prevents interstitial fibrosis and diastolic dysfunction, we speculate about a potential benefit for EPA-Ffar4 signaling in heart failure preserved with ejection fraction. Graphical abstract: Highlights: ω3-PUFA cardioprotection is concentration dependent. EPA prevents remodeling associated with HF. EPA signals through Ffar4 to prevent cardiac fibrosis. EPA-Ffar4 signaling could be a novel therapeutic approach for HFpEF.